2021
DOI: 10.1371/journal.pone.0252330
|View full text |Cite
|
Sign up to set email alerts
|

Human click-based echolocation: Effects of blindness and age, and real-life implications in a 10-week training program

Abstract: Understanding the factors that determine if a person can successfully learn a novel sensory skill is essential for understanding how the brain adapts to change, and for providing rehabilitative support for people with sensory loss. We report a training study investigating the effects of blindness and age on the learning of a complex auditory skill: click-based echolocation. Blind and sighted participants of various ages (21–79 yrs; median blind: 45 yrs; median sighted: 26 yrs) trained in 20 sessions over the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 43 publications
0
44
0
1
Order By: Relevance
“…Thus, although previous research has shown that blind echolocation experts performed better than blind participants on both of these tasks of auditory localization (Tonelli et al 2020 ; Vercillo et al 2015 ), we did not find evidence supporting the idea that performance improved with echolocation training in blind people. It is important to note that this null effect is not due to a limited ability of participants to learn click-based echolocation—in fact, participants’ performance in click-based echolocation improved in three different echolocation tasks (size discrimination, orientation identification, virtual navigation) to a level that in most (but not all) cases matched performance demonstrated by experts (Norman et al 2021 ; and Supplementary Material S1). Thus, significant improvement in click-based echolocation ability over the course of 10 weeks was not sufficient to confer improvements in auditory localization ability.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, although previous research has shown that blind echolocation experts performed better than blind participants on both of these tasks of auditory localization (Tonelli et al 2020 ; Vercillo et al 2015 ), we did not find evidence supporting the idea that performance improved with echolocation training in blind people. It is important to note that this null effect is not due to a limited ability of participants to learn click-based echolocation—in fact, participants’ performance in click-based echolocation improved in three different echolocation tasks (size discrimination, orientation identification, virtual navigation) to a level that in most (but not all) cases matched performance demonstrated by experts (Norman et al 2021 ; and Supplementary Material S1). Thus, significant improvement in click-based echolocation ability over the course of 10 weeks was not sufficient to confer improvements in auditory localization ability.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a 10-week period might not be long enough for the effects to take place. Related to this, even though training led to a dramatic improvement in echolocation ability in all participants, highest performance was achieved only at the end, and performance did not match the performance of experts in all tasks [e.g., in the size discrimination task, participants did not perform as well as experts even after 10 weeks of training, see Norman et al ( 2021 )]. Thus, it is possible that more training or longer periods of use of this skill might be needed to achieve effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations